Petrographic characteristics of deep marine turbidite sandstones of the Upper Cretaceous Tanjero Formation, Northwestern Sulaimaniyah, Iraq: Implications for provenance and tectonic setting - Çelik, Hasan; Hama Salih, Hemin Muhammad (General Directorate of Mineral Research and Exploration (MTA), 2021)
This study was carried out to determine the sedimentary provenance of Upper Cretaceous turbidites of Tanjero Formation. The sandstone portion of the unit has been examined based on field and laboratory studies. Seven sections were measured and described in detail on the perfectly cropped out part of the unit at the southern limb of the Sulaimaniyah Syncline. The thickness of the measured sections varies from 120 m to 192 m. The measured sections start from the top of the underlying Shiranish Formation to the syncline axis in the Tanjero Formation. For petrographic analysis sixtynine representative rock samples were collected. Modal analysis and ternary diagrams point out that, the sandstones are calclithite (litharenite), very fine to medium grained in size consisting of chert, siltstone, mudstone, radiolarian chert and radiolarian mudstone fragments, angular to subangular in shape, very poorly to moderately sorted, transported over short distances and represent submature stage. Grain contact types and high contact index (4.7) indicate moderate to tightly packing, moderate compaction. Transported broken neritic fossil shells, moderately rounded glauconite grains, and undefinable fossils in the altered carbonate rock fragments indicate that the tectonic provenance, lithic recycle category, composed of not only the clastics as interpreted in previous studies derived from Lower Cretaceous Qulqula (radiolarian) Formation which represents deep marine, but also it revealed that a sedimentary formation must also exist in the source area, which is the Lower Cretaceous Balambo Formation. © 2021 General Directorate of Mineral Research and Exploration (MTA). All rights reserved.
Keywords: Iraq; Northwestern Sulaimaniyah; Provenance; Sedimentary petrography; Tanjero Formation